Sodium hypochlorite as an oxidizing agent for removal of soil organic matter before microplastics analyses. Issue 1 (25th January 2022) - Bottone, Anna; Boily, Jean‐Francois; Shchukarev, Andrey; Andersson, Patrik L.; Klaminder, Jonatan
Abstract: The omnipresence of microplastics (MPs) across Earth's surface has raised concerns about their environmental impact and created an urgent need for methods to identify them in complex soil and sedimentary matrices. However, detecting MPs in the O horizons of soils is difficult because plastic polymers share many physical and chemical properties with natural soil organic matter (SOM). In this study, we assessed whether sodium hypochlorite (NaOCl), a reagent that can oxidize SOM and simultaneously preserve mineral constituents, can be used for MP analysis and characterization in soil environments. In addition, we scrutinized how factors such as MP size, polymer type, extraction methods, and soil matrix affect the recovery of microplastic particles. We used both hydrophobic and density‐dependent separation methods to assess the effects of our oxidation treatment on the recovery of MP. We observed that NaOCl effectively removed SOM without greatly altering the surface properties of resistant MP polymers (polypropylene, polylactic acid, low‐density polyethylene, and polyethylene terephthalate), which were characterized using scanning electron microscopy and Fourier‐transform infrared spectroscopy after SOM removal. The NaOCl treatment caused some chlorination and formation of additional C–OH bonds on polymer surfaces, which likely contributed to the reduced efficiency of the hydrophobic‐based (oil) extraction. We conclude that NaOCl treatment can improve detection of MPs in SOM‐rich soil and that recovery of MPs from soils is influenced by MP size, polymer type, extraction method, and soil type, which makes it challenging to develop a universal analytical method. Core Ideas: Sodium hypochlorite (NaOCl) induces a chlorination of the polymer surface. NaOCl at room temperature reduces interference from humus during microplastic separation. NaOCl treatment can remove organics but preserve polymers and soil minerals. Recovery of microplastics depends on polymer type, size, extraction method, and soil type.